USING SOCIAL MEDIA AS A LEARNING MEDIA OF FOREIGN LANGUAGE STUDENTS IN HIGHER EDUCATION - Agung Rinaldy Malik; Muhammad Nur Ashar Asnur (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2019)
ABSTRACT Foreign language is an important component of someone in facing the era of Industry 4.0. The development of Information and Communication Technology (ICT) will have an impact on the creation of a learning media innovation that will facilitate users in the learning process in higher education. Likewise in foreign language learning. Online-based learning has been designed in such a way as to increase learning knowledge and motivation. This study uses a qualitative approach with the survey method. Data and Sources of data in this study are students of foreign language study programs at universities in Indonesia. The results of the study show that students generally always use smartphones and use social media in all their activities. Students use a lot of social media in exploring vocabulary and increasing vocabulary mastery, learning as well as building networks for native speakers (Muttersprachler), and making social media a means of learning by accessing foreign-language songs and interesting media in student foreign language learning. Thus social media can be one of the means of education for students which ends in improving foreign language skills. Keywords: Social Media, Learning Media, Learning Foreign Languages, Higher Education